Optimal Scheduling of Demand Side Load Management of Smart Grid Considering Energy Efficiency - Balouch, Shoaib; Abrar, Muhammad; Abdul Muqeet, Hafiz; Shahzad, Muhammad; Jamil, Harun; Hamdi, Monia; Malik, Abdul Sattar; Hamam, Habib (Frontiers in Energy Research, 2022)
The purpose of this research is to provide power grid energy efficiency solutions. In this paper, a comprehensive review and its optimal solution is proposed considering the various challenges of smart grid demand-side management. The main technique is based on a novel idea in the Smart Grid – demand response Optimization which enables autonomous energy management on the demand side for a wide variety of customers. The first section of this research examines the smart grid issue and evaluates the state-of-the-art load management techniques in terms of the work's scope. The demand-side load management architecture consists of three primary levels, two of them in line planning and low-cost scheduling, while the third layer, demand response which is a significant expansion of this domain. The implementation of the proposed architecture in MATLAB/Simulink, with test results demonstrating significant of the proposed solution.